Virtual Rehabilitation of the Paretic Hand and Arm in Persons With Stroke: Translation From Laboratory to Rehabilitation Centers and the Patient's Home - Fluet, Gerard; Qiu, Qinyin; Patel, Jigna; Mont, Ashley; Cronce, Amanda; Yarossi, Mathew; Merians, Alma; Adamovich, Sergei (Frontiers in Neurology, 2021)
The anatomical and physiological heterogeneity of strokes and persons with stroke, along with the complexity of normal upper extremity movment make the possibility that any single treatment approach will become the definitive solution for all persons with upper extremity hemiparesis due to stroke unlikely. This situation and the non-inferiority level outcomes identified by many studies of virtual rehabilitation are considered by some to indicate that it is time to consider other treatment modalities. Our group, among others, has endeavored to build on the initial positive outcomes in studies of virtual rehabilitation by identifying patient populations, treatment settings and training schedules that will best leverage virtual rehabilitation’s strengths. We feel that data generated by our lab and others suggest that 1) persons with stroke may adapt to virtual rehabilitation of hand function differently based on their level of impairment and stage of recovery and 2) that less expensive, more accessible home based equipment seems to be an effective alternative to clinic based treatment that justifies continued optimism and study.